Theoretical Elaboration of Quantitative Data - Barney G. Glaser (Grounded Theory Review: An International Journal)
Quantitative data is so closely associated with the current emphasis on verification that its possibilities for generating theory have been left vastly underdeveloped. However, some of our best monographs based on quantitative data indicate that they can be a very rich medium for discovering theory. In these monographs, discovery cannot be stopped, but breaks through both verifications and preconceived conceptual schemes to provide us with very interesting and important theory. Yet, since the authors are still so focused on testing provisionally what they have discovered, their work is mostly written in the hedging rhetoric of verification. The result is that their statements present tests as merely "plausible suggestions." The plausibly suggested test should not be construed with our goal of the purposeful generating and suggesting of theory. The generating capacities of these sociologists and the richness of their research are, therefore, not given the fullest impetus.